E-service composition for decision support, based on monitoring of contamination processes and analysis of water resource data - Dzemydienė, Dalė; Maskeliūnas, Saulius; Miliauskas, Arūnas; Naujikienė, Ramutė; Dzemydaitė, Giedrė (Technological and Economic Development of Economy, 2015)
Our research concerns the development of a unified coherent framework for evaluating water contamination processes and solving environment protection problems according to sustainable development requirements. The research investigations are made according to the requirements of the European Union (EU) Water Framework Directive and Sustainable Development Strategy. The article describes the decision support processes, based on integration of distributed data warehouses that are on the responsibility of different institutions. The Water Resource Management Information System became the kernel component of a decision support system. We analyse the possibilities of composing e-services in a semi-automatic way for decision support by analysing data processes in the water management sector. We would like to show the possibilities of integrating of data into a web portal from the distributed databases of the water management sector. The information infrastructure of e-service provision is constructed by ensuring the requirements of interoperability. The composition mechanisms of e-service are based on SOA, i.e. service-oriented architecture, and the Goal-Based Service Framework idea. The results are demonstrated on wastewater discharges from farms and household production into surface waters of Lithuanian districts during the period of 2003–2012 years. The water resource management domain specification is based on the goal-based service ontology.